(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
In order to improve the blood compatibility of Poly (Ethylene Terephthalate) (PET) fabric purposed for an artificial heart valve sewing ring, the grafting of Acrylic Acid (AA) and Polyethylene Glycol (PEG) on PET fabric by Ultraviolet (UV) irradiation has been studied. The influences of UV irradiation time, UV irradiation intensity and the concentration of acrylic acid have been investigated. The results revealed that acrylic acid was successfully grafted onto the surface of PET fabric and the blood compatibility of PET fabric was effectively improved. The blood compatibility tests suggested that UV irradiation method can effectively induce PEG onto the surface of AA modified PET to further prolong the Activated Partial Thromboplastin Time (APTT), Prothrombin Time (PT) and Thrombin Time (TT).